Correlation between electrical properties and critical behavior in La₀.₇Ca₀.₂₅Ag₀.₀₅MnO₃ nanoparticles - Nam, Pham Hong; Bach, Ta Ngoc; Bau, Le Viet; Dang, Nguyen Van; Tho, Pham Truong; Phuc, Nguyen Xuan; Phong, Pham Thanh (Vietnam Journal of Science and Technology, 2025)
In this study, we investigated the critical behavior of La₀.₇Ca₀.₂₅Ag₀.₀₅MnO₃ nanoparticles by analyzing temperature-dependent resistivity data and systematic magnetization measurements performed under an applied magnetic field of 3 T. The critical exponents extracted from the resistivity scaling near the ferromagnetic–paramagnetic transition, β = 0.676 and γ = 0.734, closely match those obtained from the Modified Arrott plot method, demonstrating good internal consistency between electrical transport and magnetic characterization approaches. To further assess the reliability and universality of the extracted exponents, the Widom scaling relation was employed, alongside a detailed examination of the magnetization scaling equations. Both analyses confirmed that the critical behavior satisfies the expected scaling constraints over a broad temperature and field range. The convergence of these independent methods provides strong evidence that long-range dipole–dipole interactions play a dominant role in governing the magnetic phase transition of La₀.₇Ca₀.₂₅Ag₀.₀₅MnO₃ nanoparticles, offering deeper insight into the mechanisms controlling their magnetic and transport properties.